The Brain-Derived Neurotrophic Factor Val66Met Polymorphism Is Associated With Female Obsessive-Compulsive Disorder: An Updated Meta-Analysis of 2765 Obsessive-Compulsive Disorder Cases and 5558 Controls - Shang, Yanan; Wang, Na; Zhang, En; Liu, Qian; Li, Hengfen; Zhao, Xiaofeng (Frontiers in Psychiatry, 2022)
Objective: Accumulated evidence has implicated that brain-derived neurotrophic factor (BDNF) gene polymorphisms play a role in the etiology of obsessive-compulsive disorder (OCD). A single nucleotide polymorphism in the coding exon of the BDNF gene at position 66, Val66Met (rs6265), is found to be associated with OCD in different populations, but results linking Val66Met with OCD have been inconsistent and inconclusive. In our study we performed a meta-analysis to further examine whether rs6265 genetic variants are involved in the etiology of OCD. Methods: By searching databases, relevant case-control studies were retrieved; using established inclusion criteria, we selected eligible studies for analysis. Results: Thirteen studies were identified that examined the association between the rs6265 polymorphism and OCD. After statistical analyses, no significant association was found between the rs6265 polymorphism and OCD (OR = 1.07, 95% CI = 1.00–1.15, P = 0.06 for genotype; OR = 1.06, 95% CI = 0.98–1.15, P = 0.15 for allele). However, in gender-specific analysis, female Val carriers might be a risk factor for OCD (OR = 1.36, 95% CI = 1.03–1.80, P = 0.03 for genotype; OR = 1.15, 95% CI = 1.01–1.32, P = 0.04 for allele). Conclusion: Our updated meta-analysis suggests that female carriers of the Val66Met BDNF polymorphism might be more suspectable to develop OCD.